(untitled) (American Journal of Islam and Society, 2012)
Although the Qur’ān calls Muslims to make peace with their enemies (Qur’ān 8:61‒62), some early Qur’ān exegetes1 interpret that to be abrogated by subsequent war verses (Qur’ān 9:5; Qur’ān 9:12‒13). This, according to a sound methodology, is a misinterpretation. So why is the Qur’ān often taken out of context on many issues, and on peace and war injunctions in particular? In other words, why does misunderstanding seem so pervasive among Muslims of different generations on different matters? This is certainly one of the most important questions in the context of intellectual discussion about the Qur’ān and Islam for at least two reasons: 1. The consequences of this question effectively undermine all genuine efforts to both divorce Qur’ān or Islam from the misconducts of some Muslims on several fronts, and to convey its universally positive messages. 2. The implications of this question appear to lend some credence to the claims and analyses of those who see the pervasive nature of this misunderstanding as truly representing Islam ‒ one that, in their eyes, has to be considered rather genuine. Here, their underlying presumption is that there is no “misunderstanding” of the Qur’ān, for the very fact of its pervasiveness means that it must be the true representation. The following are some honest attempts to offer a much-needed explanation in the face of these two potent and critical observations, but not as a way to justify the problem. Although the pervasive nature of misunderstanding the Qur’ān may be overplayed (one always finds dissenting voices that tend to offer more logical and supported opinions ‒ in this case, al-Ṭabarī or Ibn al-ʻArabī, the Jurist), it is true that Muslims rarely acknowledge it as a problem, hardly address it adequately, or even contemplate its negative implications for Islam. The misguided understanding of the verses of peace and war, for example, came about through a delicate interplay of at least three factors ‒ namely, interpretive methodology, cultural environment, and ideological pursuits ‒ each of which is analyzed below ...